Post-fledging behavioral ecology of migratory songbirds: how do fledgling activity rates vary across species?. (15th January 2022) - Jones, Todd M; Ward, Michael P
Abstract: Despite a large literature on the ontogeny of animal behavior, our understanding of behavioral development in young songbirds remains relatively poor. This is particularly true for the post-fledging period, where it is often difficult to follow and observe small, freely moving fledglings for extended periods of time. Fortunately, technological advances have enabled more robust examinations of songbird post-fledging behaviors. To provide greater insight into fledgling developmental and behavioral ecology, we used automated radio-telemetry systems to document post-fledging activity rates of juveniles across 9 songbird species of east-central Illinois, USA. Specifically, we sought to examine differences in the ontogeny of activity rates across species, and compare activity rates to intrinsic (e.g. morphological traits, age) and extrinsic (e.g. predation risk, brood size) factors that have the potential to influence fledgling behavior. While post-fledging activity rates differed by species, our findings show remarkable similarities in the ontogeny of fledgling activity across the avian community; all species exhibited a steady increase in activity rates with post-fledging age, with rates leveling off roughly 3 to 4 weeks post-fledging. These general patterns mirrored rates of post-fledging mortality (primarily due to predation) across the period, including the presence or absence of a post-fledging bottleneck, in which species with bottlenecks exhibit slight declines in activity rates during the first few days out of the nest. Alongside fledgling age and mortality risk, our findings also suggest that juvenile wing development and brood size at fledging mediate fledgling activity rates within and across species. Abstract : Nature favors young animals to be less active when the environment is more dangerous. We show that across songbird species, recently fledged young ("fledglings") were less active during the post-fledging period when mortality risk was high. Additionally, fledglings with more developed wings and from larger broods exhibited higher post-fledging activity rates; likely due to improved locomotor (flight) abilities and from increased sibling competition over food provided by their parents.